Aesthetic Surgical Crown Lengthening Procedure - Pablo Santos de Oliveira; Fabio Chiarelli; José A. Rodrigues; Jamil A. Shibli; Vincenzo Luca Zizzari; Adriano Piattelli; Giovanna Iezzi; Vittoria Perrotti (Hindawi Limited, 2015)
The aim of this case report was to describe the surgical sequence of crown lengthening to apically reposition the dentogingival complex, in addition to an esthetic restorative procedure. Many different causes can be responsible for short clinical crown. In these cases, the correct execution of a restorative or prosthetic rehabilitation requires an increasing of the crown length. According to the 2003 American Academy of Periodontology (Practice Profile Survey), crown lengthening is the most habitual surgical periodontal treatment.